2361. Timing of antiretroviral therapy prior to diagnosis of cryptococcal meningitis. (15th December 2022) - Chang, Bickey; Wele, Abduljewad; Atoma, Bethlehem; Kagimu, Enock; Muzoora, Conrad; Musubire, Abdu; Boulware, David R; Meya, David
Abstract: Background: Cryptococcal meningitis (CM) is the most common cause of meningitis in adults in Sub-Saharan Africa (SSA), causing significant morbidity and mortality in people living with HIV. Early initiation of antiretroviral therapy (ART) after cryptococcal diagnosis is associated with increased mortality. With increasing access to ART in SSA, an increasing proportion of CM patients are now presenting on ART, and outcomes remain unclear. Methods: We performed a retrospective study of 724 participants with positive CSF cryptococcal antigen in four clinical trials performed in Uganda from June 2017 to February 2022. We compared survival outcomes based on ART experience at the time of CM diagnosis. We had implemented structured ART interruption when ART had recently been initiated (< 2weeks). Results: Sixty-one percent (445/724) of participants were ART-naïve at the time of CM diagnosis. Compared to those receiving ART, those ART-naïve had lower CD4 counts and higher Cryptococcus colony forming units (CFUs)/mL on quantitative CSF culture (p< 0.001). However, the two-week mortality between ART-naïve and ART-experienced groups did not statistically differ (16.6% vs. 16.8%, Hazard Ratio = 0.97 (95%CI, 0.67–1.40) as well as for ten-week mortality (25.4% vs. 26.2%, Hazard Ratio = 0.98 (95%CI, 0.73–1.31)). Further stratification of ART-experienced participants by length of ART experience (< =2 weeks vs. >2 weeks prior to diagnosis) and ART continuation status (ART continued vs. discontinued if ART started < =2 weeks prior to diagnosis) demonstrated no statistically significant difference between the groups for two- or ten-week mortality. Conclusion: Cryptococcal diagnosis after ART initiation is now increasingly common. In this study, we found no significant mortality differences between ART-naïve and ART-experienced participants at 2 weeks and 10 weeks. Accounting for length of ART experience did not change these short-term mortality outcomes. One potential limitation of our study is different CM treatment regimens were used across clinical trials. Disclosures: All Authors : No reported disclosures.